Pedagogical Opportunities For Developing Students’ Emotional Intelligence Based On An Axiological Approach - Ashraf Alliyarov (Indonesian Journal Publisher, 2026)
This study examines the pedagogical possibilities of developing students’ emotional intelligence through an axiological (value-oriented) approach. The research aims to determine how value-based principles integrated into educational processes influence students’ emotional awareness, self-regulation, empathy, and value-based behavior. The study employs theoretical analysis, comparative synthesis, and an interpretative review of contemporary pedagogical and psychological literature on emotional intelligence and value education. The findings demonstrate that the axiological approach enhances emotional intelligence development by embedding moral values, personal meaning, and reflective learning practices into teaching and learning activities. Value-oriented educational environments foster deeper emotional awareness, responsible emotional regulation, and the formation of empathetic and socially responsible behavior among students. The integration of axiological principles into classroom interaction, curriculum design, and pedagogical communication supports students’ ability to understand emotions not only as psychological reactions but also as ethically and socially meaningful experiences. The study concludes that effective development of emotional intelligence requires a value-centered educational framework alongside methodological and instructional strategies. The axiological approach provides a coherent pedagogical basis for linking emotional development with moral orientation, personal meaning, and reflective learning, thereby strengthening students’ emotional competence in modern educational contexts.